IgG4-Related Disease With Testicular Involvement: A Case Report and Review of Literature - Wang, Gang; Zhuo, Ning; Luo, Xiaowen; Tian, Feng; Wen, Zhenhua; Li, Jingyang (Frontiers in Immunology, 2021)
Immunoglobulin G4-related disease (IgG4-RD) is an autoimmune inflammatory disease characterized by infiltration of IgG4+ plasma cells that can simulate a tumor manifesting as a tumor-like mass. This disease involves the pancreas, biliary tract, kidneys, salivary glands, lymph nodes, aorta, and retroperitoneum amongst other organs. However, testicular involvement is a rare entity in this disease. The treatment of testicular involvement in IgG4-RD is currently controversial. We present the case of a 65-year-old man with swelling and pain in his right scrotum three months ago. On examination, a mobile mass of approximately 2 cm in diameter was found in the right scrotum. Serological tests showed elevated levels of IgG4 and negative for tumor markers. Enhanced computed tomography of the scrotum showed a nodular hyperdense shadow with a diameter of approximately 23 mm on the right epididymis. Pathological biopsy of the right epididymis showed infiltration of plasma cells, lymphocytes, and a few neutrophils. IgG4+ plasma cells stained positive, with an IgG4/IgG ratio of more than 50% and more than 50 IgG4+ plasma cells per high-power field. A diagnosis of IgG4-RD involving the testicles was made. Prednisone 30 mg/d was given for three weeks. No scrotum swelling or pain was observed at the follow-up after six months. IgG4-related disease should be considered whenever a mass-like lesion with typical histomorphologic features involving multiple organs/anatomical sites is encountered. The testicles are an important male reproductive organ, especially for young male patients with fertility requirements. For patients with IgG4-RD testicular involvement, surgical or medical treatment requires further study.